Textbook Ownership and Knowledge Among Final-Year Nursing Students in Gorontalo - Maryadi Maryadi; Erwin Purwanto; Sartika Sartika; Nur Ayun R Yusuf (Universitas Duta Bangsa Surakarta, 2026)
Understanding biostatistics is one of the essential foundations in nursing science. This is because it is closely related to the development of evidence-based nursing. This study aimed to assess nursing students’ knowledge of biostatistics. This descriptive analytic study was conducted among final-semester nursing students in November 2025. The sample size in this study was 64 participants, calculated using the Slovin formula with a 10% margin of error. Samples were selected using a consecutive sampling technique to examine students’ knowledge based on age, gender, semester, university admissions, personal biostatistics reference, and seminar/workshop experience. Descriptive and correlational data analyses were performed using SPSS version 22 software. The results of this study indicate that most students have good knowledge of biostatistics, and there is a significant correlation between ownership of personal biostatistics textbooks and students’ knowledge (p= 0.040). The findings of this study provide information for both students and institutions regarding the benefits of owning personal biostatistics references on knowledge and understanding. This may serve as a consideration when recommending personal ownership of references, given greater access to knowledge.